KRITIK SOSIAL DALAM PUISI â€œKARANGAN BUNGAâ€ KARYA TAUFIK ISMAIL - Krisna, Avni Amelia Putri; Qur'ani, Hidayah Budi (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2021)
AbstractLiterary work, especially poetry, is an effective form of work in delivering social criticism. Literary works often describe the social reality that exists around the author's environment. Taufik Ismail's literary works carry a lot of themes that are full of social criticism in the life problems of the Indonesian people. In addition to the theme of social criticism, Taufik Ismail's poetry literature also focuses on moral, social, political, cultural, love, and religious themes. The objective of this research is to describe the social criticism contained in the poem "Karangan Bunga" by Taufik Ismail. This type of research used to examine the poetry text "Karangan Bunga" by Taufik Ismail is a qualitative descriptive study. The data source used was a poem by Taufik Ismail entitled "Karangan Bunga" which was published in 1966. The results of the study obtained the following conclusions: 1) social criticism of the government, 2) social criticism of security forces, and 3) social criticism as symbol of grief of the people.Â Â AbstrakKarya sastra khususmya puisi, merupakan salah satu bentuk karya yang efektif dalam penyampaian kritik sosial. Karya sastra seringkali mengambarkan tentang realitas sosial yang ada di sekitar lingkungan pengarang. Karya sastra Taufik Ismail banyak mengangkat tema-tema yang sarat dengan kritik sosial dalam masalah kehidupan rakyat Indonesia. Selain tema tentang kritik sosial, karya sastra puisi karya Taufik Ismail juga mengangkat tema moral, sosial, politik, budaya, percintaan, dan agama. Â Tujuan yang ingin dicapai dalam penelitian ini yaitu mendeskripsikan kritik sosial yang terdapat dalam puisi â€œKarangan Bungaâ€ karya Taufik Ismail. Jenis penelitian yang yang digunakan untuk mengkaji teks puisi â€œKarangan Bungaâ€ karya Taufik Ismail adalah penelitian deskriptif kualitatif. Sumber data yang digunakan adalah puisi karya Taufik Ismail yang berjudul â€œKarangan Bungaâ€ yang diterbitkan pada tahun 1966. Hasil penelitian memperoleh kesimpulan sebagai berikut: 1) kritik sosial terhadap pemerintah, 2) kritik sosial terhadap aparat keamanan, dan 3) kritik sosial sebagai lambang duka rakyat.